Efficacy and Tolerability of a Nutraceutical Combination (Red Yeast Rice, Policosanols, and Berberine) in Patients with Low-Moderate Risk Hypercholesterolemia: A Double-Blind, Placebo-Controlled Study - Stefano Gonnelli, MD; Carla Caffarelli, MD, PhD; Kostantinos Stolakis, MD; Claudia Cuda; Nicola Giordano, MD; Ranuccio Nuti, MD (Elsevier, 2015)
Background: Statins are at the forefront of strategies to manage hypercholesterolemia. However 10% to 15% of patients are intolerant to any statin drugs, even at low daily doses and almost one-third of statin users discontinue therapy within 1 year. Some nutraceuticals are prescribed as lipid-lowering substances, but doubts remain about their efficacy and tolerability. Objectives: We aimed to investigate the efficacy and the safety of a nutraceutical combination consisting mainly of 200 mg red yeast rice extract (equivalent to 3 mg monacolins), 500 mg berberine, and 10 mg policosanols (MBP-NC) in patients with low-moderate risk hypercholesterolemia. Methods: In this single centre, randomized, double-blind, placebo-controlled study 60 consecutive outpatients (29 men and 31 women; age range = 18-60 years), with newly diagnosed primary hypercholesterolemia not previously treated, after a run-in period of 3 weeks on a stable hypolipidic diet, were randomized to receive a pill of MBP-NC (n = 30) or placebo (n = 30) once a day after dinner, in addition to the hypolipidic diet. The efficacy and the tolerability of the proposed nutraceutical treatment were fully assessed after 4, 12, and 24 weeks of treatment. Results: In the MBP-NC group both total cholesterol and LDL-C already showed a significant reduction at Week 4 (-30.3% ± 33.9% and -29.4% ± 35.3%, respectively) that remained substantially unchanged at Week 12 (-26.7% ± 33.1% and -25.6% ± 31.5%, respectively) and at Week 24 (-24.6% ± 32.1% and -23.7% ± 32.6%, respectively). The between-groups differences were significant at all time points for both total cholesterol and LDL-C. There were no significant changes in HDL-C, fasting glucose, and triglyceride serum levels in either group. MBP-NC was also safe and well tolerated. Conclusions: In patients with low- to moderate-risk hypercholesterolemia a nutraceutical combination in association with a hypolipidic diet significantly reduced total cholesterol and LDL-C levels and may favor the reaching the recommended cholesterol targets. ClinicalTrials.gov identifier: NCT02078167.